Tree and forest management in floodplains of the Peruvian Amazon - Jong, W. de (2001)
This paper discusses different tree and forest management strategies in Yanallpa, a ribereno village located within the Ucayali floodplain, Peru. In the village, studies on tree and forest management were conducted through surveys, participative observation and unstructured interviews with farmers. Farmers in the floodplain rely on a mixed portfolio of agricultural production, including tree and forest management. Fields in which tree or forest management occur are of two types: Forest gardens in which a large number of species are being produced, and fields in which annual crops are combined with one or several tree species. Within each of these two categories distinctive tree or forest management strategies are recognized. In forest gardens, tree production is the main economic activity. On agricultural field especially in the lower elevations that have the more fertile soils, trees may be grown in addition to annual or semi-perennial crops. Two species, Cedrela odorata and Calycophyllum spruceanum are prominently managed in the latter field types. It appears, however, that the specific tree composition of the fields is closely related to the alternative options of crop-production on those fields. These alternative options are largely related to the biophysical condition of these fields. Tree and forest management appears to be an appropriate option as part of floodplain agriculture, but options have to be adapted to the specific circumstances that different sites offer.